Optimization of Secondary Metabolite Production in the Sponge Associated Bacterium Roseivirga sp. PAP.19 Using the OSMAC Approach - Pradani, Andin Syamsi; Harwoko, Harwoko; Meinita, Maria Dyah Nur; Riviani, Riviani; Mettal, Ute; Riyanti (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract  Highlight Research Compounds produced by Roseivirga PAP.19 bacteria have potential as antimicrobials. The OSMAC approach was used successfully to activate BGCs of Roseivirga PAP.19. The use of medium in bacterial culture affects the secondary metabolites produced by Roseivirga PAP.19 bacteria. Bacteria cultured in A1Bfe+C medium produced more secondary metabolites compared to the other medium. The different incubation times during culture affect the amount of secondary metabolite compounds produced.   Abstract Marine sponge-associated bacteria are a rich source of bioactive metabolites. The biochemical interaction between bacteria and sponges enables symbiotic bacteria to produce metabolites similar to those of their host. Metabolite extracts from symbiotic bacteria contain bioactive compounds with cytotoxic, antiviral, and antimicrobial properties. There is an urgent need for new antimicrobial agents due to the increasing resistance to existing drugs. This study aims to optimize the medium and incubation time of secondary metabolites produced by the symbiotic bacteria of the sponge Roseivirga sp. PAP.19. To stimulate biosynthesis of silent gene clusters, the One Strain Many Compounds (OSMAC) approach was used. Bacteria were cultured in various media and at different incubation times. This has the potential to increase the production of secondary metabolites. Secondary metabolites were analyzed using LC-HRMS. The potential of these metabolites as antimicrobial agents was subsequently evaluated. Results showed six compounds with antimicrobial potential. Notably, the A1BFe+C medium produced more bioactive compounds than the other medium, and the highest compound production occurred on day 4. These findings suggest that optimizing culture conditions using the OSMAC approach can enhance the yield of potentially valuable antimicrobial secondary metabolites from symbiotic bacteria, which may contribute to the discovery of new antimicrobial agents.